Hubungan Antara Kualitas Informasi pada Media Digital IISMA Alumni Club dengan Sikap Anggota terhadap Peluang Berkarier di Luar Negeri - Nafla Calya Firdani; Hanny Hafiar; Anwar Sani (Jurnal Sosial Humaniora dan Pendidikan, 2026)
IISMA Alumni Club actively shares overseas career information through Instagram (@iisma_ac) and the WhatsApp group “IISMA AC Career Community”, yet many graduated members still choose domestic careers. This study examines the relationship between information quality on IISMA Alumni Club's digital media and graduated members' attitudes toward overseas career opportunities, using Information Integration Theory, where information quality comprises valence and weight. Using a quantitative correlational approach, data from 96 randomly sampled respondents were analyzed with the Rank Spearman correlation test in SPSS. Results show a strong, significant positive relationship between information valence and weight with members' cognitive, affective, and conative attitudes. The strongest relationship was between valence and the affective aspect (rs = 0.683), while the weakest was between weight and the conative aspect (rs = 0.597). The study concludes that information quality on IISMA Alumni Club's digital media is significantly related to members' attitudes toward overseas careers, though the conative aspect shows a comparatively lower relationship.